Neuroprotective Effects of MAGL (Monoacylglycerol Lipase) Inhibitors in Experimental Ischemic Stroke. Issue 3 (March 2018) - Choi, Sang-Ho; Arai, Allison L.; Mou, Yongshan; Kang, Byeongteck; Yen, Cecil Chern-Chyi; Hallenbeck, John; Silva, Afonso C.
Abstract : Background and Purpose—: MAGL (monoacylglycerol lipase) is an enzyme that hydrolyzes the endocannabinoid 2-arachidonoylglycerol and regulates the production of arachidonic acid and prostaglandins—substances that mediate tissue inflammatory response. Here, we have studied the effects of the selective MAGL inhibitors JZL184 and MJN110 and their underlying molecular mechanisms on 3 different experimental models of focal cerebral ischemia. Methods—: SHR (spontaneously hypertensive rats) and normotensive WKY (Wistar Kyoto) rats were subject to an intracortical injection of the potent vasoconstrictor endothelin-1, permanent occlusion of a distal segment of the middle cerebral artery via craniectomy, or transient occlusion of the middle cerebral artery by the intraluminal suture method. JZL184 or MJN110 was administered 60 minutes after focal cerebral ischemia. Infarct volumes, hemispheric swelling, and functional outcomes were assessed between days 1 to 28 by magnetic resonance imaging, histology, and behavioral tests. Results—: Pharmacological inhibition of MAGL significantly attenuated infarct volume and hemispheric swelling. MAGL inhibition also ameliorated sensorimotor deficits, suppressed inflammatory response, and decreased the number of degenerating neurons. These beneficial effects of MAGL inhibition were not fully abrogated by selective antagonists of cannabinoid receptors, indicating that the anti-inflammatory effects are caused by inhibition of eicosanoid production rather than by activation of cannabinoid receptors. Conclusions—: Our results suggest that MAGL may contribute to the pathophysiology of focal cerebral ischemia and is thus a promising therapeutic target for the treatment of ischemic stroke. Abstract : Supplemental Digital Content is available in the text.